PELATIHAN PERMAINAN EDUKATIF UNTUK ANAK BERBASIS KOMPUTER PADA GURU DAN SISWA DI TK KATOLIK MALAEKAT PELINDUNG KOTA MANADO - Irene R H T Tangkawarow (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Computer as a media learning is owned by TK Katolik Malaekat Pelindung in Manado city. However, limited knowledge of software application for early childhood makes computer studies at TK Malaekat Pelindung Kota Manado are often ineffective implemented.This situation causes stimulation for the child's intelligence are not fully achieved due to application of the games which used is unfit to the stage of early childhood development. The aims of this activity are: (1) To provide knowledge and understanding of the educational games application that correspond to the teachers and students at TK Katolik Malaekat Pelindung in Manado City. (2) To provide training for teachers and students on how to operate GCompris application. GCompris application is qualified educational games application which consists ofattractive interface, easy to use, and variety games inside. This training uses resident expert method. Resident expert method is a method of training with guidance from expert in information systems (in this case, the expert on the application GCompris).